GEOLOGI DAN ANALISIS TEKTONIK DAERAH KAMPAR SUMATRA TENGAH - -, Faizal Muhamadsyah; -, Iyan Haryanto (Fakultas Teknik Geologi Universitas Padjadjaran, 2008)
Central Sumatera basin controlled by an amount of regional stike-slip fault (wrench fault) moving on transtensinal system. Overall srike-slip pattern forming as negative flower structure, yielding horst and garben. This tecotonic process happened in Early Miocene.Graben forming begin the sedimentation process which indicate the coarse clastica deposit existence that goes on fluvial environment. This deposit equivalent with Sihapas formation that have an age of Eosen. The Sedimentary basin had a subsidence continuously till Middle of Miocene, that indicated by developt marine sedimentary rock.In Plio-Pleistocene, the uplifting processes is happen again that cause forming of fold and fault structure. Tectonic compression cause the research area more shallow and then become a continent. This is indicated by developted conglomerate, sandy conglomerate, tuffaceous sandstone which forming in continent.